Inferring alterations in cell‐to‐cell communication in HER2+ breast cancer using secretome profiling of three cell models. Issue 9 (18th April 2014) - Klinke, David J.; Kulkarni, Yogesh M.; Wu, Yueting; Byrne‐Hoffman, Christina
ABSTRACT Challenges in demonstrating durable clinical responses to molecular‐targeted therapies have sparked a re‐emergence in viewing cancer as an evolutionary process. In somatic evolution, cellular variants are introduced through a random process of somatic mutation and are selected for improved fitness through a competition for survival. In contrast to Darwinian evolution, cellular variants that are retained may directly alter the fitness competition. If cell‐to‐cell communication is important for selection, the biochemical cues secreted by malignant cells that emerge should be altered to bias this fitness competition. To test this hypothesis, we compared the proteins secreted in vitro by two human HER2+ breast cancer cell lines (BT474 and SKBR3) relative to a normal human mammary epithelial cell line (184A1) using a proteomics workflow that leveraged two‐dimensional gel electrophoresis (2DE) and MALDI‐TOF mass spectrometry. Supported by the 2DE secretome maps and identified proteins, the two breast cancer cell lines exhibited secretome profiles that were similar to each other and, yet, were distinct from the 184A1 secretome. Using protein–protein interaction and pathway inference tools for functional annotation, the results suggest that all three cell lines secrete exosomes, as confirmed by scanning electron microscopy. Interestingly, the HER2+ breast cancer cell line exosomes are enriched in proteins involved in antigen‐processing and presentation and glycolytic metabolism. These pathways are associated with two of the emerging hallmarks of cancer: evasion of tumor immunosurveillance and deregulating cellular energetics. Biotechnol. Bioeng. 2014;111: 1853–1863. © 2014 Wiley Periodicals, Inc.